2018
DOI: 10.36062/ijah.57.2.2018.219-224
|View full text |Cite
|
Sign up to set email alerts
|

Semen characteristics in young and adult Surti buck

Abstract: Present study was conducted to study the effect of age on semen parameters in Surti buck. Age was significantly influenced on majority of the semen parameters in Surti bucks. Adult bucks significantly (P<0.01) performed better in terms of semen quantitative parameters viz., semen density (3.91+0.03 vs 3.79+0.03), volume (1.01+0.03 vs 0.86+0.03 mL), sperm concentration (2564.22+87.27 vs 1978.13+60.79 million/mL), total sperm count (2483.83+115.22 vs 1546.93+62.96 million) and semen index (1737.19+78.10 vs 1104.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…This study corroborates reports by Atara et al (2018), who found the volume of semen in Surti bucks is higher in adults compared to young. Likewise, Suyadi (2012) finds semen volume does not differ between age groups of Boer bucks.…”
Section: Characteristics Of Semen Semen Volumesupporting
confidence: 93%
See 2 more Smart Citations
“…This study corroborates reports by Atara et al (2018), who found the volume of semen in Surti bucks is higher in adults compared to young. Likewise, Suyadi (2012) finds semen volume does not differ between age groups of Boer bucks.…”
Section: Characteristics Of Semen Semen Volumesupporting
confidence: 93%
“…Suyadi (2012) finds there are no significant differences in sperm concentrations based on buck age. In contrast, Atara et al (2018) determined age-based differences on sperm concentration.…”
Section: Sperm Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The individual motility in the present study is in close harmony with Patil et al (2019). In contrary, higher values of individual motility was noted by Atara et al (2018) in Surti goat. These differences of sperm motility might be due to variation in breed, nutrition, environment and individual variation (Umar et al, 2017).…”
Section: Resultsmentioning
confidence: 59%